2021
DOI: 10.1007/s00402-021-03968-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel minimally invasive tape suture osteosynthesis for instabilities of the pubic symphysis: a biomechanical study

Abstract: Introduction Open book fractures are challenging injuries oftentimes requiring surgical treatment. The current treatment of choice is symphyseal plating, which requires extensive surgery and entirely limits physiological movement of the symphyseal joint, frequently resulting in implant failure. Therefore, we investigated the biomechanical properties of a semi-rigid implant (modified SpeedBridge™) as a minimally invasive tape suture construct for the treatment of open book fractures and evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 32 publications
(58 reference statements)
2
20
0
Order By: Relevance
“…A rigid fixation of the pubic symphysis restricts the normal physiological movement. Cavalcanti Kußmaul et al performed a biomechanical study, which confirmed that symphyseal plating as a rigid osteosynthesis almost entirely compromised the physiological mobility of the symphyseal joint [ 12 ]. In the long run, physiological micromotion may stress the metalwork of the symphysis, resulting in a gradual increase in the symphyseal space and implant failure, such as screw loosening or plate breakage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A rigid fixation of the pubic symphysis restricts the normal physiological movement. Cavalcanti Kußmaul et al performed a biomechanical study, which confirmed that symphyseal plating as a rigid osteosynthesis almost entirely compromised the physiological mobility of the symphyseal joint [ 12 ]. In the long run, physiological micromotion may stress the metalwork of the symphysis, resulting in a gradual increase in the symphyseal space and implant failure, such as screw loosening or plate breakage.…”
Section: Discussionmentioning
confidence: 99%
“…The goals of treating a symphysis diastasis include an appropriate reduction and a stable fixation to provide pelvic ring stability, which can effectively diminish the pain, and permit early mobility [ 6 – 8 ]. Numerous surgical methods have been described for treating pubic symphysis diastasis, including plating, external fixation, tension band wiring, sutures, and percutaneous fixation [ 6 , 9 – 12 ]. Previous biomechanical studies have indicated that symphysis plating is effective in restoring the anterior ring stability [ 13 ], and it has often been used to treat cases of pubic symphysis diastasis worldwide [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another, potentially biomechanically superior, option could be the insertion of minimally invasive Tape-Suture constructs: these constructs have demonstrated sufficient biomechanical stability while allowing the above-mentioned micromovements of the pubic symphysis as shown by previous studies of our group [ 36 ].…”
Section: Discussionmentioning
confidence: 96%
“…Currently, cranial visualization of the pubic rim and retraction of the bladder remains the favored approach for safety reasons. Beside plating or trans-obturatorial cable fixation other innovative stabilization techniques for the pubic symphysis were described in the past 43 45 . Chen et al published an article about 45 patients with pubic disruption, treated using percutaneous screw fixation.…”
Section: Discussionmentioning
confidence: 99%